Impact of surgical treatment of benign prostate hyperplasia on lower urinary tract symptoms and quality of life - Babic, Uros M; Soldatović, Ivan; Vuković, Ivan; Dragićević, Svetomir; Djordjević, Dejan; Aćimović, Miodrag; Šantrić, Veljko; Džamić, Zoran; Vuksanović, Aleksandar (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Benign prostatic hyperplasia (BPH) is a pathological process, which is one of the most common causes of so-called lower urinary tract symptoms (LUTS). LUTS affect many aspects of daily activities and almost all domains of health-related quality of life (HRQoL). The objective of this study was to evaluate the effects of operative treatment of BPH using standard clinical diagnostic procedures and effects on LUTS using the symptom-score validated to Serbian language as well as implications on HRQoL. Methods. Seventy-four patients underwent surgical treatment for BPH. The study protocol included objective and subjective parameters of the following sets of variables measured before and after the surgery: voiding and incontinence symptoms were measured using the International Continence Society male Short Form (ICS male SF) questionnaire, HRQoL was measured using the SF-36 questionnaire along with standard clinical measurement of residual urine and urine flow. Results. After the surgery, all patients had decrease of voiding scores (13.5 ± 3.3 before and 1.5 ± 1.4 after surgery) and incontinence symptoms (5.7 ± 3.9 before and 0.6 ± 0.8 after surgery) in comparison to period before operative treatment. Significant improvements in all dimensions of HRQoL were noticed, particularly in emotional health. Although mental and physical total scores were significantly better than prior to the surgery, the level of improvement of voiding and incontinence scores were significantly correlated only with the level of improvement of mental score. Conclusion. After BPH surgery, patients are likely to have normal voiding symptoms, barely some involuntary control over urination and overll better HRQoL, particularly in emotional domain.
Keywords: prostatic hyperplasia; urologic surgical procedures; preoperative care; postoperative period; quality of life; surveys and questionnaires